Penerapan Hukum Dalam Pertimbangan Hakim Untuk Menjatuhkan Putusan Dalam Perkara Pidana Terhadap Korban Anak - Hidayat, Nofan; Aji, Rihantoro Bayu; Taufiqurrahman, Taufiqurrahman (Universitas Wijaya Putra, 2023)
The crimes of sexual abuse against children often use social networks to fool his victims in various crimes. The average victim is a child under the age and the perpetrator is an adult, the crime sexual abuse causes deep trauma for the victim and require a long time to eliminate it to the children. With the absence of law, perpetrators of sexual abuse against children could be criminalized if they meet the elements as stated in the Criminal Code (KUHP) and the Child Protection Act. The method of approach in the research was used is the approach of the law of normative-empirical approach and legislation (statue approach), conceptual approach and the case approach. The results of this study stated that the panel of Judges aggravate the punishment against the Defendant by taking attention to the relationship between the Defendant and the victim as the students and teachers in educational institutions. In the verdict of the trial with the case of the crime of sexual abuse, the Defendant demanded punishment with Article 82 section (1) Jo Article 76E Law Number 35 of the year 2014 concerning amendment to Law Number 23 of the Year 2002 about Child Protection, Jo Article 82 section (4.5) and the article is additional regulation Number 01 of the year 2016 on the second amendment to Law Number 23 of the Year 2002 about Child Protection, jo Law Number 17 of the Year 2016 On the Determination of Government Regulation in Lieu of Law Number 01 of the year 2016 on amendment to Law Number 23 of the Year 2002 On Child Protection with the threat of criminal for 20 (twenty) years and a fine of Rp 1.000.000.000,- this is because the Defendant is an educators/ educators, where should the defendant gave teachings, or education and provide a safe and comfortable against children, especially the victims of the crime of sexual abuse.